Cover Picture: Biotechnology Journal 12/2018. Issue 12 (10th December 2018) - Unknown
Abstract : Lipid tubules are of particular interest for many potential applications in nanotechnology. Among various techniques for the material fabrication, the morphological regulation by proteins mimicking biological processes may provide the chances to form with highly‐tuned structures. This cover shows the enhancement of membrane tubule formation through the interaction between MamY protein isolated from magnetotactic bacteria and an anionic phospholipid, cardiolipin. This is reported by Masayoshi Tanaka, Thanawat Suwatthanarak, Atsushi Arakaki, Benjamin R. G. Johnson, Stephen D. Evans, Mina Okochi, Sarah S. Staniland, Tadashi Matsunaga in article1800087 .